Μελέτη της αντίδρασης καταλυτικής οξύδωσης ξενοβιοτικών ενώσεων σε νερό με χρήση οξυγόνου (O2) παρουσία υδρογόνου (H2) - Μιχαήλ, Φλωρεντία (Τμήμα Επιστήμης και Τεχνολογίας Περιβάλλοντος, Σχολή Γεωτεχνικών Επιστημών και Διαχείρισης Περιβάλλοντος,Τεχνολογικό πανεπιστήμιο Κύπρου, 2013)
This thesis was prepared at the Department of Environmental Science and Technology, at Cyprus University of Technology. Had a total duration of one year and was conducted under the supervision of Professor Costas N. Costa. The thesis consists of four chapters. In the first chapter, which is the theoretical part it refers to a catalytic effect, the law based metal catalysts and chemical adsorption. Also, the method of catalyst composition applied in this work (wet impregnation method), and physicochemical methods for the characterization of solid catalysts used. The details of these techniques include the use of ultraviolet spectroscopy (Ultra Violet, UV) and visible (Visible, VIS) and identify specific surface (B.E.T.). In addition, the first chapter includes a brief literature review for the study of Catalytic Oxidation Reaction xenobiotic compounds in water using oxygen in the presence of hydrogen. In the second chapter, which is the experimental part describes the experimental procedure followed for the synthesis and characterization of three supported catalysts studied. In addition, details the experimental apparatus used to carry out catalytic experiments. The next chapter presented and analyzed the results obtained from experiments measuring the behavior and catalytic characterization of the studied catalysts in the catalytic oxidation reaction of xenobiotic compounds in water using hydrogen in the presence of oxygen and the total organic carbon (TOC). In the fourth and final chapter presents the conclusions drawn from the experimental results of this work.
Keywords: Chemical methods; Techniques include; Physicochemical methods